Ethical Perspectives on Mental Health Advocacy for College Students at Risk of Suicide: Insights from Buddhist Psychology - Prastowo, Fuji Riang; Yuniarti, Kwartarini Wahyu; Yulianti, Yulianti (Universitas Gadjah Mada, 2025)
This study examines the ethical aspects of mental health advocacy for Indonesian university students atrisk of suicide, highlighting the constraints of prevailing Western psychological frameworks that emphasize biomedical secrecy and autonomy. These standardized techniques can engender estrangement and overlook Indonesian students’ cultural and community realities. This study utilizes an autoethnographic approach rooted in Buddhist psychology and the concept of cognitive justice to demonstrate how academic settings influenced by cognitive capitalism exacerbate mental health issues. The research presents an ethical alternative grounded in Buddhist principles, including Bodhicitta (altruistic intention), Anattā (non-self), and Kalyāṇamitta (spiritual friendship), emphasizing community healing and relational support. Lecturer-counselors are essential figures, delivering non-clinical, culturally relevant support that connects institutional procedures with students’ real-life experiences. The study attempts inflexible confidentiality standards in Western mental health procedures, contending that they may heighten suicide risk by isolating peers and family from the support process. It presents a three-tiered structure integrating universal prevention, targeted ethical support, and culturally tailored crisis intervention, harmonizing Buddhist ethical principles with global health standards. This integrative strategy reconceptualizes mental health advocacy as a moral and community pursuit, converting higher education institutions into compassionate ecosystems grounded in ethical solidarity, cognitive equity, and cultural significance. The study ultimately calls for transitioning to ethically inclusive, spiritually coherent,and structurally responsive mental health interventions in Indonesian universities.